Effect of antihypertensive medication reduction vs usual care on short-term blood pressure control in patients aged ≥ 80 years with hypertension: the OPTiMISE randomized clinical trial - Sheppard, JP; Burt, J; Lown, M; Temple, E; Lowe, R; Fraser, R; Allen, J; Ford, GA; Heneghan, C; Hobbs, FDR; Jowett, S; Kodabuckus, S; et al. (American Medical Association, 2020)
Importance: Deprescribing of antihypertensive medications is recommended for some older patients with polypharmacy and multimorbidity when the benefits of continued treatment may not outweigh the harms.